A Phase I, Randomized, Controlled Clinical Study of CC-11050 in People Living With HIV With Suppressed Plasma Viremia on Antiretroviral Therapy (APHRODITE). (3rd June 2019) - Boulougoura, Afroditi; Gabriel, Erin; Laidlaw, Elizabeth; Khetani, Vikram; Arakawa, Ken; Higgins, Jeanette; Rupert, Adam; Gorelick, Robert J; Lumbard, Keith; Pau, Alice; Poole, April; Kibiy, Angela; et al.
Abstract: Objective: Phosphodiesterase 4 inhibitors (PDE4i) are novel anti-inflammatory medications that have been approved for rheumatologic diseases and have been tested as host-directed therapy in tuberculosis. We examined the safety of CC-11050, a potent PDE4i in people living with HIV (PLWH) with suppressed HIV plasma viremia. We hypothesized that CC-11050 could be used to modulate HIV-related inflammation. Method: Thirty PLWH on antiretroviral therapy (ART) ≥ 1 year with suppressed HIV viremia were enrolled and randomized 2:1 to 12 weeks of CC-11050 200mg twice daily or placebo with follow-up at weeks 2, 4, 8, 12, and 16. Primary endpoint was safety. Secondary endpoints were the effect of CC-11050 on cytokines, monocyte, and T-cell activation and potential pharmacokinetic interaction between CC-11050 and Efavirenz (EFV). Results: At baseline, median age was 49.5 years and CD4 count 459 cells/µL. Most frequent adverse events (grade 1 and 2 only) in CC-11050 group were headache, diarrhea, nausea, cough, nasal congestion, and restlessness. Over a 12-week period, the CC-11050 group had lower level of IL-8, adjusted for baseline level, group, and week (0.72-fold, P = .02), lower percentage of NK cells (0.87-fold, P = .02) and higher IL-6 level (1.48-fold, P = .03) compared to placebo (0.87-fold, P = .02 ). CC-11050 and EFV co-administration did not reveal any pharmacokinetic interaction. Conclusions: CC-11050 was well tolerated in PLWH, without affecting CD4 counts or plasma viremia, and led to a decrease in NK cells and plasma IL-8 level after 12-weeks of administration. Further study will be needed to elucidate the efficacy of CC-11050 as potential anti-inflammatory adjuvant strategy in HIV. Abstract : In a phase 1, randomized, placebo-controlled, double-blinded clinical trial, CC-11050, a potent phosphodiesterase 4 inhibitor, was tested in people living with HIV who had suppressed plasma viremia on antiretroviral therapy. The drug was safe and well tolerated without affecting CD4 counts or viremia and with some evidence of biologic activity including decreases of NK cells and plasma IL-8 levels.